2019
DOI: 10.21053/ceo.2018.01011
|View full text |Cite
|
Sign up to set email alerts
|

Role of Immunohistochemistry in Fine Needle Aspiration and Core Needle Biopsy of Thyroid Nodules

Abstract: Objectives Immunohistochemistry (IHC) has been used for the diagnosis of indeterminate results in fine needle aspiration (FNA) of thyroid nodules. However, the role of IHC in core needle biopsy (CNB) is not clear and the efficacy of testing for molecular markers following CNB has not been evaluated. The aim of this study is to compare the role of IHC staining in CNB with that in FNA when examining thyroid nodules and to compare the sensitivity and usefulness of different molecular markers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
(19 reference statements)
0
8
0
1
Order By: Relevance
“…We searched papers published in English in PubMed and found only one focusing on this topic. In this paper, Song et al reported that the continued indeterminate rate was 42.9% for FNB and 11.3% for CNB after IHC was applied[14]. In our study, all 72 indeterminate samples of CNB could be determined with the help of IHC, although the accuracy of each marker was different.…”
mentioning
confidence: 57%
“…We searched papers published in English in PubMed and found only one focusing on this topic. In this paper, Song et al reported that the continued indeterminate rate was 42.9% for FNB and 11.3% for CNB after IHC was applied[14]. In our study, all 72 indeterminate samples of CNB could be determined with the help of IHC, although the accuracy of each marker was different.…”
mentioning
confidence: 57%
“…We searched papers published in English in PubMed and found only one focusing on this topic. In this paper, Song et al reported that the continued uncertain rate was 42.9% for FNB and 11.3% for CNB after IHC was applied [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association of additional markers (eg, galectin-3) can improve its Sn to 94%, with a high negative predictive value (92%) retaining moderate Sp and positive predictive value (73% and 50%, respectively). This can be of help to rule out follicular carcinoma in cytology when both are negative 26 27…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%